Preliminary study on micropropagation of hylocereus polyrhizus with waste coconut water and sucrose - Ng, Zhe-Cheng; Tan, Suat Hian; Shiekh Mahmud, Siti Hamidah Radiyah; Ma, Nyuk Ling (Trans Tech Publications, 2019)
Mature coconut water is always been thrown away as a waste. However, it contain a lots of nutritional elements such as amino acids, pytohormones and minerals. Plant needs some essential nutrients besides pytohormones for their growth and development. In this study, the effect of waste mature coconut water and sucrose was observed on the micropropagation of dragon fruit tree (Hylocereus polyrhizus). The stem was inoculated on MS medium containing Benzyleaminopurine (BAP) 0.03mg/L BAP and 0.01mg/L Naphthaleneacetic acid (NAA) supplemented with waste mature coconut water in various concentrations (0%, 2%, 4% and 6% v/v) and with various concentrations : 0%, 1%, 2% and 3% of sucrose respectively. As the concentration of the waste mature coconut water and sucrose increased up to 4 % and 3%, increase in the elongation of the stem and the number of root regenerated per explant was observed repectively. In conclusion, waste mature coconut water has enhanced the elongation of the shoots but has not promoted on the root induction with the suitable amount of sucrose.